Evaluasi Hasil Klinis Pada Tim Medis yang Mendapat Vaksinasi Booster di Rumah Sakit Bengkayang Kalimantan Barat - Lukas, Stefanus; Ramatillah, Diana Laila; Aldi, Yufri; Wahyuni, Fatma Sri; Paulina, Ida; Gloria, Fransisca; Michael, Michael (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Abstract: In reducing the risk of transmission to health workers, the Government has given the 3rd Booster Covid-19 Vaccination since August 2021. This study uses the Astra Zeneca Vaccine, Moderna Vaccine and Pfizer Vaccine. The purpose of this study was to evaluate the effectiveness of the 3rd Booster vaccine and the clinical outcomes of post-vaccination health workers at West Kalimantan Hospital. Research method Observational Cross-sectional Prospective by conducting questionnaires and interviewing health workers. Samples were taken by convenience sampling and statistical analysis of chis-square. The research instrument used a questionnaire distributed in the hospital. In the study, it was found that as many as 12.60% (14 out of 118 health workers) were infected with Covid-19. The habit that influenced the effectiveness of the 3rd booster vaccination was sunbathing (p <0.05). The low severity of health workers infected with Covid-19 after the 3rd booster vaccine can be seen from the place of treatment, namely 97% independent isolation, 60% without using antivirals and 77% without using antibiotics. The type of vitamin that is most widely used is vitamin C. Hence with this booster vaccination aims to prevent and reduce the severity of patients who contract Covid-19 after vaccination.